The regulation of transporting the bodies of the dead over the border of Ukraine in Administrative Law - Федотов, Олексій Павлович; Федотов, О. П.; Fedotov, Oleksii P.; Fedotov, O. P.; Сурілова, Олена Олексіївна; Сурілова, О. О.; Surilova, Olena O.; Surilova, O. O. (Одеса : Гельветика, 2019)
Статтю присвячено характеристиці положень законодавства України, якими регламентовано порядок перевезення тіл померлих через кордон України та врегульовано питання охорони здоров’я і гарантування санітарно-епідеміологічної безпеки населення, організації патологоанатомічної та судово-медичної експертизи з метою надання необхідних документів для переміщення тіл загиблих через митний кордон України. Встановлено, що хоча статистика переміщень через митний кордон України тіл померлих є незначною (а щодо транзитних перевезень таких тіл взагалі рідкісною), усе ж таке переміщення здійснюється, а у зв’язку зі зростаючою мобільністю населення та ризиками, що виникають внаслідок цього та мають тенденцію до зростання, постає необхідність у правовому врегулюванні питань, пов’язаних із таким переміщенням, а також систематизації відповідного законодавства.

The article is devoted to the characterize the provisions of the legislation of Ukraine, that regulate the procedure of transportation over the border of Ukraine of the bodies of the dead and regulate the questions, connected with protection of health and ensuring the sanitary-epidemiological well-being of the population, arranging pathoanatomical and forensic medical examination in order to provide the necessary documents when moving bodies of those who have died through the customs border of Ukraine. It has been established that although the statistics of movements of the bodies of the dead across the customs border of Ukraine are insignificant (and in relation to transit traffic of such bodies of the dead in general rare), this movement is still carried out, but due to increasing mobility of the population and the risks arising from it and tend to to growth, there is a need for a legal settlement of issues related to such a move, as well as to systematize the relevant legislation.
Fedotov O. P. The regulation of transporting the bodies of the dead over the border of Ukraine in Administrative Law / O. P. Fedotov, O. O. Surilova // Юридичний вісник. - Одеса : Гельветика - 2019. - № 2. - С. 53-61.
Keywords: transportation of bodies of dead; death certificate; funeral business; state border; sanitary well-being; sanitary-epidemiological control; Research Subject Categories::LAW/JURISPRUDENCE; транспортування тіл померлих; свідоцтво про смерть; похоронна справа; державний кордон; санітарний стан; санітарно-епідеміологічний контроль